1986
DOI: 10.2307/1938516
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Interactions Among Four Species of the Salamander Genus Desmognathus

Abstract: Four sympatric species: Desmognathus quadramaculatus, D. monticola, D. fuscus, and D. ochrophaeus, showed different substrate preferences in experimental trials. In addition, the choices of substrates and of cover objects were influenced by the presence of other salamanders. Significant differences in substrate choice were found for each pair of species. The ratio of rocky to woody substrate chosen was lower for the more terrestrial species. The ecologically intermediate species, D. monticola, exhibited the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 15 publications
0
15
1
Order By: Relevance
“…In eastern United States forests, salamanders typically comprise the greatest biomass of any vertebrates (Burton and Likens, 1975;Petranka and Murray, 2001;Peterman et al, 2008) and serve a key role in the ecosystem because they consume invertebrates and serve as prey for other vertebrates. While numerous studies have documented the importance of competition and predation in structuring stream salamander assemblages and their distributions (e.g., Southerland, 1986b;Hairston, 1987;Roudebush and Taylor, 1987), relatively fewer studies have examined the importance of environmental factors in undisturbed habitats. Of these studies, Keen (1984) found that dusky salamanders (Desmognathus fuscus) were found under smaller rocks more frequently on high moisture than low moisture substrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In eastern United States forests, salamanders typically comprise the greatest biomass of any vertebrates (Burton and Likens, 1975;Petranka and Murray, 2001;Peterman et al, 2008) and serve a key role in the ecosystem because they consume invertebrates and serve as prey for other vertebrates. While numerous studies have documented the importance of competition and predation in structuring stream salamander assemblages and their distributions (e.g., Southerland, 1986b;Hairston, 1987;Roudebush and Taylor, 1987), relatively fewer studies have examined the importance of environmental factors in undisturbed habitats. Of these studies, Keen (1984) found that dusky salamanders (Desmognathus fuscus) were found under smaller rocks more frequently on high moisture than low moisture substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Eastern red-backed salamanders (P. cinereus), which were presumably superior competitors, inhabited isolated pockets were soil moisture was higher and forced the Shenandoah salamanders (P. shenandoah) to reside in the much drier talus slopes. In the southern Appalachians, Southerland (1986b) found that the larger black-bellied salamanders (D. quadramaculatus) predation of juvenile seal salamanders (D. monticola) sharply reduced survival and caused shifts in activity and habitat selection. In the 149 plots that we encountered stream salamanders, only 11 of these plots had salamanders of two or more species.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that creek chubs actively interfere with salamanders to prevent access to resources via aggressive encounters. Aggression has been observed between spring salamanders and brook trout (Resetarits, 1991), and Desmognathus salamanders will avoid habitats to reduce the potential of negative interactions with more aggressive salamander species (Southerland, 1986a). Our study did not allow us to evaluate which mode of competition is responsible because we did not make systematic observations to quantify aggressive behaviors, an area of focus for our future research.…”
Section: Discussionmentioning
confidence: 99%
“…This result was interpreted as a non-lethal behavioral response to a predator. Southerland (1986a) conducted substrate choice and refuge sharing experiments in an ensemble of four desmognathans, D. quadramaculatus, D. monticola, D. fuscus, and D. orestes. He reported shifts in habitat choice in response to congeners, which varied according to species and body size.…”
Section: The Four Arenas Of Interactionmentioning
confidence: 99%